Comparison of Psychological Disorders in Vaccinated and Non-Vaccinated COVID-19 Patients - Abdul Rehman, Omar Murtaza Sheikh, Sara Mehboob, Ghulam Shabir Shaikh, Shahid Iqbal, Muhammad Ali Ranjha (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
The COVID-19 pandemic has resulted in both physical and mental healthchallenges worldwide. While vaccination efforts focus primarily on reducing the severity and spread of the virus, there